The effects of strength training on muscle architecture in humans - Kawakami, Y. (International Journal of Sport & Health Science, 2005)
The present paper reviews previous studies on changes in muscle architecture in humans as a result of strength training. Muscle architecture here refers to 1) muscle size, 2) pennation angle, and 3) muscle fiber length. Training-induced changes are summarized respectively. A typical outcome of strength training is muscle hypertrophy, which is manifested as an increase in muscle size evaluated by cross-sectional area and muscle volume. However, changes also occur in pennation angles and, possibly, in muscle fiber lengths. Increased pennation angles after training have the detrimental effect of producing a reduced force transmission from muscle fibers to tendon, which might lead to a decrease in specific tension or muscle force per physiological cross-sectional area. Recent in vivo studies on human muscles have revealed that changes in pennation angles resulting from training and contraction are much greater than previously thought.